THE INFLUENCE OF AUDIO-VISUAL MEDIA ON YOUNG WOMEN'S KNOWLEDGE IN MAINTAINING THE CLEANLINESS OF GENETALIA EQUIPMENT DURING MENSTRUATION IN KALURAHAN WUKIRHARJO, KALASAN, SLEMAN DIY - Duwi Yuliyanti; Ayu Fitriani (Jurnal Scientia, 2023)
The lack of knowledge of young women about how to keep the genitals clean during menstruation is one of the causes of various health problems due to poor sanitation during menstruation. Based on a preliminary study at Losari II Subvillage Wukirharjo Village that has been done as many as 8 out of 10 young women have less knowledge, with the percentage of correct answers between 30-50% and the other 2 have sufficient knowledge with the percentage of correct answers 60% and 70%. A total of 5 young women experienced itching and irritation in the pubic area during menstruation. As many as 9 young women smelled an unpleasant odor in the pubic area during menstruation. This study aimed to determine the effectiveness of audio-visual media in increasing young women's knowledge of maintaining the cleanliness of the genital organs during menstruation. This research design is one group pre and post test. The population of this study were all female adolescents of Padukuhan Losari II who had menstruated. The sampling technique in this study was Total Sampling with reference to the inclusion criteria with a sample of 36 people. The results of this study indicate that before the intervention, the knowledge of respondents was in the good category 2 people (5.6%), enough 29 people (80.6%), and less than 5 people (13.8%). After the intervention, the respondents' knowledge increased, the good category became 28 people (77.8%), the moderate category decreased to 8 people (22.2%), and there were no respondents who had less knowledge (0.0%), with the Asymp value. Sig (2 tailed) 0.000 < 0.05. From the results of this study, it can be concluded that providing health education using audio-visual media affects the knowledge of young women in Padukuhan Losari II Kalurahan Wukirharjo in maintaining the cleanliness of the genital organs during menstruation. The results of this study are expected to be a guideline for young women to always maintain the cleanliness of the genital area properly and correctly, especially during menstruation. For Padukuhan Losari II, recommends more health education using audio-visual media.